Individual Learning Reflection - Sirathamwanich, Saranphak (2014)
In the real business world, there is an opportunity for new start-up entrepreneur to develop their own business idea and launch it to the real market. However, some risks may exist because they might not have sufficient knowledge and direct experience in relation to their product or service. To help solving this problem, we are encouraged to involve in a simulated entrepreneurial environment where people are able to improve systematical skill and develop an ability to think creatively in a safe environment. This business plan offers me an opportunity to integrate my knowledge since first degree till MBA program along with professional experience to learn and develop my business idea to become a concrete business project.